Komparasi Algoritma Data Mining Untuk Akurasi Penentuan Beasiswa Kurang Mampu IAIN Syekh Nurjati Cirebon - Arif Maulana (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
The scholarships reserved for students who are economically disadvantaged to pay the cost of study in college. The number of criteria used for the determination of scholarships made it difficult to make a decision on granting a scholarship. Besides the time it takes too long. The purpose of this study is the classification of students are not able to Decision Tree, k-NN, NN, which uses the algorithm C4.5. Classification results are evaluated and validated using the area under the curve (AUC) of the ROC curve. Given this comparison can facilitate and accelerate decision-making to provide scholarships for students can not afford.